Comportamiento informacional y políticas públicas de información: consideraciones teóricas alrededor del caso de DATASUS en Brasil - Berrío-Zapata, Cristian; de Assis-Rodrigues, Fernando [UNESP]; de Cássia Cassiano-Lopes, Rita [UNESP]; Grossi de Carvalho, Angela Maria [UNESP]; Gonçalves-Santana, Ricardo Cesar [UNESP] (Universidad Nacional Autonoma de Mexico, 2016)
The information age requires information policies to guide its global articulation. Brazil has attempted to answer this call with policies that despite their good intentions have not obtained desired results. DATASUS, the Brazilian health information system, operates under policies that seem to be designed without considering the latest discoveries of Information Science regarding the informational nature of humans. This article discusses several information behavior models and theories that must be considered when formulating information policies and proposes an “Information Field” model containing guideposts for their construction.
Informational behavior and public information policies: theoretical considerations arising from the case of DATASUS in Brazil
Keywords: Brazil; e-government; Information Policy; Information Systems; Internet